Chin Augmentation Techniques: A Systematic Review. Issue 5 (20th December 2022) - Oranges, Carlo M.; Grufman, Vendela; di Summa, Pietro G.; Fritsche, Elmar; Kalbermatten, Daniel F.
Abstract : Background: Chin augmentation has maintained a high level of popularity among patients and facial plastic surgeons. Several procedures exist to enhance the appearance of a small chin. The aim of this study was to perform a systematic literature review to determine outcomes and complications associated with the different techniques described. Methods: MEDLINE, PubMed, PubMed Central (PMC), and Cochrane Central Registry of Controlled Trials (CENTRAL) databases were screened using a search algorithm. The techniques were classified, and related outcomes and complications tabulated and analyzed. Results: A total of 54 studies on primary chin augmentation published from 1977 to 2020 met inclusion criteria, representing 4897 treated patients. Six main surgical techniques were identified: chin augmentation with implants (silicone, Gore-Tex, Mersilene, Prolene, Medpor, Proplast, hard tissue replacement, porous block hydroxyapatite, or acrylic; n = 3344), osteotomy ( n = 885), autologous grafts (fat, bone, derma, or cartilage; n = 398), fillers (hyaluronic acid, hydroxyapatite, or biphasic polymer; n = 233), local tissue rearrangements ( n = 32), and a combination of implant placement and osteotomy ( n = 5). All techniques provided consistently satisfactory cosmetic outcomes. The overall complication rate of the most represented groups was 15.7% for implants and 19.7% for osteotomy, including 2.4% and 16.4% cases of transient mental nerve–related injuries, respectively. Conclusions: All described chin augmentation techniques achieved good outcomes with high patient satisfaction. Thorough knowledge of each technique is essential to minimize each procedure's specific complications. Caution is generally needed to avoid nerve injuries and potential overcorrection or undercorrection.